APLIKASI PEMESANAN MENU DI SUSHI TEI PLAZA SENAYAN DENGAN QR CODE BERBASIS WEB - Wismarita Gulo; Ines Heidiani Ikasari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Sushi Tei is a restaurant that serves authentic Japanese food using fresh and high quality ingredients. In improving the quality of its business, Sushi Tei must follow developments, namely technological developments. Because when a customer comes to the restaurant, then the customer will make an order and wait for the ordered food. However, when the restaurant is busy being visited by customers, the restaurant waiter is overwhelmed because they have to give a menu list book and record the food and beverage menu ordered by the customer, after that to the kitchen to deliver the customer's order and there are other problems. Based on these problems, a system was created that can make it easier to order food and drink menus at Sushi Tei without the need to call the waiter to ask for a menu list book or record the menu to be ordered. In order to minimize the occurrence of ordering errors, save time, save paper. The system is in the form of a website that will prepare menus online. This website can be done to order menus by scanning the QR Code listed on the table where the customer is occupying, then the restaurant waiter only needs to wait from the admin data which will display any orders ordered by the customer. The method used is by using a website based on a database that is connected from the customer to the server. So that this system can be used to view and order menus at the restaurant, customers can also find out the total price they have to pay.